Effectiveness of Health Education Program for Type 2 Diabetes Mellitus Patient's Self-efficacy toward Managing Feet at Endocrinology and Diabetes Center in Al-Rusafa Sector - Gabish, amer; mohammed, widad (Iraqi National Journal of Nursing Specialties, 2018)
Objective(s): to assess the effectiveness of educational program on improving diabetic foot self-efficacy concerning managing their feet. Methodology: A descriptive analytic (quasi – experimental) design study was carried out at Diabetic and Endocrinology Center in Baghdad- Rusafa Sector from 2nd of May 2017, to27th June 2018. Non-probability sample of (80) male and female diabetic patients were selected. The study instruments consisted of two major parts: first part related to sociodemographic characteristic and the second part is related to diabetic foot self-efficacy. The researcher examined the patients’ self-efficacy by introducing the pre-test then, the teaching program of three lectures was given. one – hour lecture was given. Afterward, the post-test. The data were analyzed by using two statistical approaches: Descriptive and Inferential statistics. Results: The study revealed that the diabetic foot self-efficacy regarding foot self-care was 60.0% (acceptable) for the post-test as opposed to the pre-test which was 37.5% (weak). Recommendation: The study recommended that type 2 diabetic patients should be encouraged to attend specific educational programs and workshops concerning diabetic foot self-care and effect of self-care to improve self-confidence